On the Economic Impacts of Transportation Innovations: A Comprehensive Application to Quantifying the Impacts of an Hyperloop Technology - Buttlar, William G; Haslag, Joseph H (The Economics and Finance Letters, 2022)
The purpose of this paper is to quantify the economic impacts associated with an investment in transportation systems. Here, we apply the methodology to projected comprehensive economic impacts of an Hyperloop route. The methodology is a low-frequency economic growth model that includes cumulative gains in real GDP, cost savings and the greenhouse gas savings of the proposed Hyperloop technology. To calibrate the model, we consider a route spanning from Texas to Chicago and covering 1,575 miles across the proposed hyperloop system. The infrastructure investment is obtained from construction cost estimates presented in previous feasibility studies. Our contribution is to present a simple general equilibrium approach to quantifying transportation economic impacts. To our knowledge, our is the first quantitative assessment of the Hyperloop technology. We include an analysis of the public finance aspects of the route, thus adding an answer to the question regarding the national merits of such an investment project. Our findings suggest that for returns comparable to the interstate highway system, the project could be paid for out of the stream of future tax revenues. There are additional gains through lower fares and travel times. Lastly, the environmental gains, especially from reduced air travel, are quantitatively significant.